2007
DOI: 10.1093/jac/dkm035
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of Lactobacillus, Pediococcus and Lactococcus human isolates and cultures intended for probiotic or nutritional use

Abstract: Finding of acquired resistance genes in isolates intended for probiotic or nutritional use highlights the importance of antimicrobial susceptibility testing in documenting the safety of commercial LAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
182
4
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(245 citation statements)
references
References 54 publications
39
182
4
9
Order By: Relevance
“…However, the resistance towards vancomycin has been demonstrated being as intrinsic (Tynkkynen et al, 1998). Lactobacilli are usually susceptible to chloramphenicol, erythromycin and clindamycin (protein synthesis inhibitors) (Coppola et al, 2005;Klare et al, 2007). In addition, resistance against trimethoprim (nucleic acid synthesis inhibitor), seems to be intrinsic (Ammor et al, 2007).…”
Section: Antibiotic Resistance Of Probiotic Lactobacillimentioning
confidence: 99%
“…However, the resistance towards vancomycin has been demonstrated being as intrinsic (Tynkkynen et al, 1998). Lactobacilli are usually susceptible to chloramphenicol, erythromycin and clindamycin (protein synthesis inhibitors) (Coppola et al, 2005;Klare et al, 2007). In addition, resistance against trimethoprim (nucleic acid synthesis inhibitor), seems to be intrinsic (Ammor et al, 2007).…”
Section: Antibiotic Resistance Of Probiotic Lactobacillimentioning
confidence: 99%
“…Characteristics such as total security for the host, resistance to gastric acidity and pancreatic secretions, adhesion to intestinal epithelial cells, antimicrobial activity, inhibition of the adhesion of pathogenic bacteria, antibiotic resistance, tolerance to food additives and stability in the food matrix, are all considered relevant in tracing the probiotic profile of a specific strain (Soccol et al 2010). Pediococci are used as beneficial microorganisms in the context of food and livestock microbiology (Haakensen et al 2009) and can be used as starter cultures or as probiotics (Klare et al 2007). P. acidilactici has interesting properties, such as resistance to heat, cold, pH, proteolytic treatments, and the capacity for the production of antimicrobial peptide (pediocin) with anti-listerial activity and antimicrobial spectrum, which makes it interesting as a food biopreservative (Papagianni and Anastasiadou 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thumu & Halami (2012) and Nawaz et al (2011) reported that many LAB resistant to erythromycin, tetracycline, and chloramphenicol related to the presence of gene encoding resistant due to mutation or mobile genes. In contrast, Klare et al (2007) reported that gram-positive bacteria are generally sensitive to antibiotics that inhibit the protein synthesis such as erythromycin and chloramphenicol. Isolates of E5, E7, and E8 did not resistant to erythromycin, chloramphenicol, and tetracycline.…”
Section: Susceptibility To Antibioticsmentioning
confidence: 99%